PERANCANGAN POROS TRANSMISI DENGAN DAYA 100 HP - Freddy Mananoma; Agung Sutrisno; Stenly Tangkuman (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2017)
The aim of this work is to design a shaft for transmitting power of 100 hp. There are two gears on the shaft, and two bearings as supports at the shaft. Based on design result, diameter of critical points on the shaft have been acquired as follows; D1=1,80 in, D2=3,40 in, D3=3,74 in, D4=5,00 in, D5=4,40 in, and D6=3,15 in. Finally, a technical drawing of the designed shaft can be made using Autocad software. Â Keywords : Diameter, Force, Design, Transmission Shaft,